Ni9S8-coated Au core-shell nanocrystal and preparation method thereof
By preparing Ni9S8@Au core-shell nanocrystals, the problem of insufficient electrochemical activity of existing nickel sulfide nanocrystals is solved, higher electrochemical activity is achieved, and its application potential in multiple fields is expanded.
Patent Information
- Application Number
- CN202411728377.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The electrochemical activity of existing nickel sulfide nanocrystals is insufficient, which limits its application in the fields of catalysis, energy storage, sensing, etc.
By preparing Ni9S8@Au core-shell nanocrystals, they were synthesized under a protective atmosphere by high-temperature thermal decomposition method to form Ni9S8 as the core-shell structure of Au as the shell, and its electrochemical activity was improved.
It improves the electrochemical activity of nickel sulfide nanocrystals and enhances its application potential in the fields of catalysis, energy storage, sensing, etc.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano-synthesis preparation, and particularly relates to a Ni9S8@Au core-shell nano-crystal and a preparation method thereof. Background Art
[0002] As the global demand for sustainable energy solutions continues to grow, nickel sulfide has attracted widespread attention due to its potential applications in electrochemical energy storage and conversion. Nickel sulfide has a unique electronic structure and chemical stability, making it a candidate for electrode materials, electrocatalysts, electromagnetic materials, and semiconductor materials.
[0003] In order to improve the various properties of nickel sulfide, researchers began to explore nano-nickel sulfide materials with novel structures and compositions. The development of nanocrystal technology provides new possibilities for the design and synthesis of nickel sulfide with specific morphology and size, and it may be combined with other active elements to produce multi-component composite nanomaterials with better performance. By precisely controlling the synthesis process of nanocrystals, nanomaterials with controllable specific surface area, pore structure, core-shell structure and special chemical bonding ability can be prepared, which is crucial for improving various electrochemical properties. Nickel sulfide can synthesize different crystal structures by adjusting the ratio of nickel and sulfur, such as NiS, NiS2 and Ni3S4. Different crystal structures have different physical and chemical properties. This diversity in composition allows for differences in the properties of the materials.
[0004] Nanocrystals of different forms exhibit different physical and chemical properties, which requires researchers to develop synthetic methods that can precisely control the morphology and phase of nanocrystals, but the precise control of these parameters in the synthesis process is still challenging. The methods for synthesizing nanocrystals are often complex and difficult to scale up, limiting their application in the field of energy storage.
[0005] Chinese invention patent CN105060353B discloses a method for preparing orthorhombic nickel sulfide nanocrystals. The electrochemical activity of the orthorhombic nickel sulfide nanocrystals obtained needs to be improved, which limits its practical application in catalysis, energy storage, sensing and other fields. Summary of the invention
[0006] In order to overcome the defects of the prior art, the object of the present invention is to provide a Ni9S8@Au core-shell nanocrystal and a preparation method thereof, so as to improve the electrochemical activity of nickelous sulfide nanocrystals.
[0007] The present invention is achieved through the following technical solutions: A Ni9S8@Au core-shell nanocrystal comprises a core and a shell wrapped outside the core, wherein the core is Ni9S8 and the shell is Au.
[0008] Preferably, in the Ni9S8@Au core-shell nanocrystals, the molar ratio of Ni9S8 to Au is 1:(1-5).
[0009] Preferably, the size of the Ni9S8@Au core-shell nanocrystals is 50-100 nm.
[0010] The method for preparing Ni9S8@Au core-shell nanocrystals of the present invention comprises the following steps: (1) mixing nickel diethyldithiocarbamate with oleylamine, 1-octadecene and 1-dodecyl mercaptan to form a uniform solution; (2) Under a protective atmosphere, heating the uniform solution to a reaction temperature, reacting to obtain a reaction solution; (3) adding a tri-n-octylphosphine solution of chloroauric acid to the reaction solution, and reacting at the reaction temperature; (4) After the reaction solution obtained in step (3) is cooled to room temperature, a mixture of a polar solvent and a non-polar solvent is added, and the solid product is separated and dried to obtain Ni9S8@Au core-shell nanocrystals.
[0011] Preferably, in step (1), the molar ratio of nickel diethyldithiocarbamate, oleylamine, 1-octadecene and 1-dodecyl mercaptan is 0.035:2:1:1.
[0012] Preferably, step (1) is specifically: mixing nickel diethyldithiocarbamate with oleylamine, 1-octadecene, and 1-dodecylmercaptan; The resulting mixture was heated to 40-60 °C for 30-60 min under vacuum to form a homogeneous solution.
[0013] Preferably, in step (2), the reaction temperature is 160-240°C, and the reaction time is 1-2 h.
[0014] Preferably, in step (3), the reaction time is 2-3 h.
[0015] Preferably, in step (4), the polar solvent is anhydrous ethanol, and the non-polar solvent is cyclohexane.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a core-shell nanocrystal Ni9S8@Au, which has a core-shell structure as a whole, wherein the core is a Ni9S8 nanoscale crystal, and the shell layer covers Au nanoparticles, and the composition is uniform. The shell Au nanoparticles have excellent electrochemical activity. Due to the unique structure and potential properties of the Ni9S8@Au core-shell nanocrystal, it has broad application potential in the fields of catalysis, energy storage, and sensing, and can be further explored by other researchers.
[0017] The present invention utilizes a synthesis method based on hot injection and high-temperature thermal decomposition to successfully prepare a nano-scale Ni9S8@Au material with a core-shell structure. In the present invention, oleylamine, 1-octadecene and 1-dodecyl mercaptan are used as solvents to provide the high temperature required for the reaction on the one hand; on the other hand, they are used as surfactants to evenly cover the surface of the nanomaterial, so that the nanomaterial grows evenly and is not easy to agglomerate. In the process of coating Au on the surface of Ni9S8, since there are exposed sulfur atoms on the surface of Ni9S8 and 1-dodecyl mercaptan covers the surface of Ni9S8, Au is easy to combine with S atoms. Therefore, in the preparation process, Au can be evenly coated on the surface of Ni9S8. The preparation method is simple and convenient, the overall synthesis time is not long, it has a high yield and good repeatability, and high-quality core-shell nanocrystal Ni9S8@Au can be obtained without using high-pressure reaction conditions. By extension, the synthesis method can also be used for the synthesis of other new core-shell structure nanomaterials, providing a novel idea for more efficient, green, convenient and low-cost preparation of new multifunctional nanomaterials.
[0018] Furthermore, by precisely controlling the synthesis conditions such as reaction temperature, reaction time and the amount of each organic reagent, the present invention can prepare nanocrystals with a size in the range of 50-100 nm. Nanomaterials of this size usually have good physical and chemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is a transmission electron microscope (TEM) image of the Ni9S8@Au core-shell nanocrystals prepared in Example 3 of the present invention.
[0021] Figure 2 The energy spectrum element mapping and mixed element mapping diagram corresponding to Ni, S, and Au of the Ni9S8@Au core-shell nanocrystals prepared in Example 3 of the present invention.
[0022] Figure 3 for Figure 2 Relative intensity plot of each element in the spectral element map.
[0023] Figure 4 This is the X-ray powder diffraction pattern (XRD) of the Ni9S8@Au core-shell nanocrystals prepared in Example 3 of the present invention.
[0024] Figure 5 X-ray photoelectron spectroscopy (XPS) analysis of different elements of the Ni9S8@Au core-shell nanocrystals prepared in Example 3 of the present invention: (a) Ni 2p; (b) S 2p; (c) Au 4f. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0026] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0027] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0028] The Ni9S8@Au core-shell nanocrystal of the present invention has a core-shell structure as a whole, wherein the core is a Ni9S8 nanoscale crystal, and the outer surface of the core is coated with Au nanoparticles, and the Au nanoparticles form an outer shell.
[0029] The size of the Ni9S8@Au core-shell nanocrystals is 50-100 nm, and the molar ratio of Ni9S8 to Au is 1:(1-5).
[0030] The method for preparing Ni9S8@Au core-shell nanocrystals of the present invention comprises the following steps: (1) mixing nickel diethyldithiocarbamate with oleylamine, 1-octadecene and 1-dodecyl mercaptan to form a uniform solution; (2) In order to prevent the reactants from being oxidized at high temperatures, the uniform solution needs to be heated to the reaction temperature under a protective atmosphere and reacted within a certain period of time to obtain a reaction solution; (3) adding a tri-n-octylphosphine solution of chloroauric acid to the reaction solution, and reacting at the reaction temperature; (4) After the reaction solution obtained in step (3) is cooled to room temperature, a mixture of a polar solvent and a non-polar solvent is added, and the solid product is separated and dried to obtain Ni9S8@Au core-shell nanocrystals.
[0031] In step (1) of the present invention, the molar ratio of nickel diethyldithiocarbamate, oleylamine, 1-octadecene and 1-dodecyl mercaptan is 0.035:2:1:1.
[0032] As a specific implementation of the present invention, the step (1) is specifically: Nickel diethyldithiocarbamate was mixed with oleylamine, 1-octadecene and 1-dodecylmercaptan in a three-necked flask; The resulting mixture was heated to 40-60 °C for 30-60 min under vacuum to form a homogeneous solution.
[0033] In step (2) of the present invention, the reaction temperature is 160-240°C and the reaction time is 1-2 h. In step (3), the reaction time is 2-3 h.
[0034] In step (4) of the present invention, the polar solvent is anhydrous ethanol, and the non-polar solvent is cyclohexane. Cyclohexane is used to remove excess non-polar surfactant oleylamine on the surface of the product. According to the principle of like dissolves like, the polar solvent anhydrous ethanol can precipitate the product coated with the non-polar surfactant. The separation method includes centrifugation at 8000 rpm for 10 minutes. The drying process can be dried in a vacuum drying oven at 65°C for 12 hours.
[0035] Example 1 This embodiment includes the following steps: (1) Mix 0.35 mmol (159.75 mg) of nickel diethyldithiocarbamate (Ni(S2CNEt2)2) precursor, 20.0 mmol of oleylamine (OM), 10.0 mmol of 1-octadecene (ODE), and 10 mmol of 1-dodecylmercaptan in a 50 mL three-necked flask; (2) After magnetically stirring the mixture of step (1), the mixture was heated to 40°C for 30 min under vacuum conditions to remove the air in the reaction system and form a uniform solution; (3) Then, the uniform solution was rapidly heated to 160 °C in a pure nitrogen atmosphere, and Ni9S8 was grown at 160 °C for 1 h to obtain a reaction solution. At the same time, 13.22 mg of chloroauric acid (HAuCl4) was ultrasonically dispersed in 2.4 g of tri-n-octylphosphine (TOP) to form a colorless and transparent HAuCl4-TOP solution; (4) Subsequently, the HAuCl4-TOP solution was injected into the reaction solution and reacted at 160 °C for 2 h; (5) After the reaction solution was rapidly cooled to room temperature, a certain amount of anhydrous ethanol and cyclohexane were added to separate the core-shell nanocrystals Ni9S8@Au. The reaction solution was then centrifuged (8000 rpm, 10 min) and the product was placed in a vacuum drying oven at 65 °C for 12 h to obtain core-shell nanocrystals Ni9S8@Au.
[0036] Example 2 This embodiment includes the following steps: (1) Mix 0.35 mmol (159.75 mg) of nickel diethyldithiocarbamate (Ni(S2CNEt2)2) precursor, 20.0 mmol of oleylamine (OM), 10.0 mmol of 1-octadecene (ODE), and 10 mmol of 1-dodecylmercaptan in a 50 mL three-necked flask; (2) After magnetically stirring the mixture of step (1), the mixture was heated to 40°C for 30 min under vacuum conditions to remove the air in the reaction system and form a uniform solution; (3) Then, the uniform solution was rapidly heated to 240 °C in a pure nitrogen atmosphere, and Ni9S8 was grown at 240 °C for 1 h to obtain a reaction solution. At the same time, 66.1 mg of chloroauric acid (HAuCl4) was ultrasonically dispersed in 2.4 g of tri-n-octylphosphine (TOP) to form a colorless and transparent HAuCl4-TOP solution; (4) Subsequently, the HAuCl4-TOP solution was injected into the reaction solution and reacted at 240 °C for 2 h; (5) After the reaction solution was rapidly cooled to room temperature, a certain amount of anhydrous ethanol and cyclohexane were added to separate the core-shell nanocrystals Ni9S8@Au. The reaction solution was then centrifuged (8000 rpm, 10 min) and the product was placed in a vacuum drying oven at 65 °C for 12 h to obtain core-shell nanocrystals Ni9S8@Au.
[0037] Example 3 (1) Mix 0.35 mmol (159.75 mg) of nickel diethyldithiocarbamate (Ni(S2CNEt2)2) precursor, 20.0 mmol of oleylamine (OM), 10.0 mmol of 1-octadecene (ODE), and 10 mmol of 1-dodecylmercaptan in a 50 mL three-necked flask; (2) After magnetically stirring the mixture of step (1), the mixture was heated to 40°C for 30 min under vacuum conditions to remove the air in the reaction system and form a uniform solution; (3) Then, the uniform solution was rapidly heated to 240 °C in a pure nitrogen atmosphere, and Ni9S8 was grown at 240 °C for 1 h to obtain a reaction solution. At the same time, 33.05 mg of chloroauric acid (HAuCl4) was ultrasonically dispersed in 2.4 g of tri-n-octylphosphine (TOP) to form a colorless and transparent HAuCl4-TOP solution; (4) Subsequently, the HAuCl4-TOP solution was injected into the reaction solution and reacted at 240 °C for 2 h; (5) After the reaction solution was rapidly cooled to room temperature, a certain amount of anhydrous ethanol and cyclohexane were added to separate the core-shell nanocrystals Ni9S8@Au. The reaction solution was then centrifuged (8000 rpm, 10 min) and the product was placed in a vacuum drying oven at 65 °C for 12 h to obtain core-shell nanocrystals Ni9S8@Au.
[0038] The Ni9S8@Au core-shell nanocrystals prepared in Example 3 were characterized by transmission electron microscopy. Figure 1 As shown in the figure, it can be seen that the obtained sample has good crystallinity. The energy spectrum element mapping and mixed element mapping corresponding to Ni, S, and Au under transmission electron microscopy are shown in the figure. Figure 2 The relative intensity of each element is shown in Figure 3 As shown. Figure 2 and Figure 3 , it can be seen that Ni and S elements are evenly distributed in the core, and Au is evenly distributed in the shell.
[0039] The core-shell nanocrystals Ni9S8@Au obtained in Example 3 were subjected to XRD phase analysis and XPS element valence analysis.
[0040] (1) X-ray powder diffraction analysis (XRD). The samples synthesized in the experiment were ground into powder using a mortar and then spread on a dedicated XRD sample stage for testing. Cu was used as the high-energy electron beam bombardment target (Cu Kα, λ = 1.5418 Å). The scanning rate of the test was 5° / min and the scanning range was 10°-70°.
[0041] The results are as follows Figure 4As shown in the figure, several main diffraction peaks in the XRD diffraction pattern of the sample are consistent with the peak positions on the PDF standard cards of Ni9S8 and Au (Ni9S8: PDF#22-1193 and Au: PDF#04-0784). According to the information on the PDF card, Ni9S8 belongs to the orthorhombic system and the crystal space group is C222 , the lattice constant is: a = 9.18 Å, b =11.263 Å, c = 9.457 Å; Au belongs to the cubic system, and the crystal space group is Fm-3m , the lattice constant is: a = b = c = 4.0786 Å.
[0042] (2) X-ray photoelectron spectroscopy (XPS). XPS was used to analyze the three elements Ni, S and Au in Ni9S8@Au core-shell nanocrystals. The three elements all had relevant peaks, proving that all three elements existed.
[0043] like Figure 5 (a) shows the deconvoluted XPS spectrum of Ni 2p, which fits well with the spin-orbit doublet and vibration satellite peaks; the two peaks with binding energy values of 853.07 and 870.72 eV represent the Ni 2+ 2p 3 / 2 and 2p 1 / 2 ; The two peaks with binding energy values of 855.92 and 874.46 eV represent Ni 3+ The existence of 2p 3 / 2 and 2p 1 / 2 state; in addition, the vibrational satellite peaks are at 861.17 and 880.55 eV, respectively. Figure 5 (b) is the XPS data curve of S in Ni9S8@Au core-shell nanocrystals. The peaks with binding energies of 161.87 and 163.01 eV correspond to 2p 3 / 2 and 2p 1 / 2 state; the peak with binding energy of 166.43 eV may be attributed to Au-S bond. The vibration satellite peaks are at 163.98 and 168.58 eV respectively. Figure 5 (c) is the XPS spectrum of Au 4f. The peaks with binding energies of 84.06 and 87.74 eV correspond to 4f 7 / 2 and 4f 5 / 2 state; the peak of binding energy at 86.86 eV is attributed to the vibrational satellite peak.
Claims
1. A Ni9S8@Au core-shell nanocrystal, characterized in that: It comprises an inner core and an outer shell wrapped around the inner core, wherein the inner core is Ni9S8 and the outer shell is Au.
2. The Ni9S8@Au core-shell nanocrystal according to claim 1, characterized in that: The molar ratio of Ni9S8 and Au is 1:(1-5).
3. The Ni9S8@Au core-shell nanocrystal according to claim 1, characterized in that: The size of the Ni9S8@Au core-shell nanocrystals is 50-100 nm.
4. The method for preparing Ni9S8@Au core-shell nanocrystals according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing nickel diethyldithiocarbamate with oleylamine, 1-octadecene and 1-dodecyl mercaptan to form a uniform solution; (2) Under a protective atmosphere, heating the uniform solution to a reaction temperature, reacting to obtain a reaction solution; (3) adding a tri-n-octylphosphine solution of chloroauric acid to the reaction solution, and reacting at the reaction temperature; (4) After the reaction solution obtained in step (3) is cooled to room temperature, a mixture of a polar solvent and a non-polar solvent is added, and the solid product is separated and dried to obtain Ni9S8@Au core-shell nanocrystals.
5. The method for preparing Ni9S8@Au core-shell nanocrystals according to claim 4, characterized in that: In step (1), the molar ratio of nickel diethyldithiocarbamate, oleylamine, 1-octadecene and 1-dodecyl mercaptan is 0.035:2:1:
1.
6. The method for preparing Ni9S8@Au core-shell nanocrystals according to claim 4, characterized in that: Step (1) is as follows: mixing nickel diethyldithiocarbamate with oleylamine, 1-octadecene, and 1-dodecylmercaptan; The resulting mixture was heated to 40-60 °C for 30-60 min under vacuum to form a homogeneous solution.
7. The method for preparing Ni9S8@Au core-shell nanocrystals according to claim 4, characterized in that: In step (2), the reaction temperature is 160-240°C and the reaction time is 1-2 h.
8. The method for preparing Ni9S8@Au core-shell nanocrystals according to claim 4, characterized in that: In step (3), the reaction time is 2-3 h.
9. The method for preparing Ni9S8@Au core-shell nanocrystals according to claim 4, characterized in that: In step (4), the polar solvent is anhydrous ethanol, and the non-polar solvent is cyclohexane.
Citation Information
Patent Citations
A kind of preparation method of orthorhombic nickel subsulfide nanocrystal
CN105060353B
Compound type negative electrode material of lithium ion battery and preparation method of material and lithium ion battery
CN103682332A
Preparation method of nano compound metal sulfide adopting core-shell structure
CN107055587A
Au / NiSx eggshell-structured nanoparticles and preparation method thereof
CN110026565A
Ni@Au core-shell type nanocatalyst as well as synthesis and application of Ni@Au core-shell type nanocatalyst
CN110756197A